Performance assessment of a cogeneration system in a sugar cane factory using energy and exergy analysis - Mostafa Abouelsoud; Mohamed Y. Khalil; Ramadan Hefny Ali; Hussein M. Maghrabie (Case Studies in Thermal Engineering)
Sugar cane is one of the most important industrial crops, providing vital products such as sugar, molasses, and bagasse. The bagasse serves as the primary fuel in cogeneration systems. This paper investigates the energy and exergy efficiencies of the entire sugar production process at the Edfu Sugar Factory in Egypt, including raw juice production, juice heating, evaporation, crystallization, and the performance of boilers, turbines, and de-superheaters. Utilizing actual operational data, the analysis identifies significant energy losses, with the raw juice production (RJP) process experiencing the highest loss at 58,959 kW, followed closely by the boilers at 52,111 kW. As well, the results indicate that boilers account for 78.38 % of the total exergy destruction in the system, revealing critical inefficiencies. Moreover, the overall energy and exergy efficiencies are 87.15 % and 66.45 %, respectively. To address inefficiencies, two modifications were proposed: replacing mechanical turbines in RJP process with direct current (DC) motors, boosting power output by 5500 kW, providing 2000 kW for grid export, and saving 163,200 $ annually; and reducing bagasse moisture by 42 % using flue gas waste heat, increasing boiler exergy efficiency by 3.82 % and overall system efficiency by 3.38 %, saving 29,376 tons of bagasse annually, valued at 763,776 $. This study is novel in its comprehensive analysis of the entire sugarcane production process at the sugar factory, offering practical solutions to mitigate high energy losses and inefficiencies. It provides valuable insights for similar industrial settings, where energy conservation is critical for both economic viability and environmental sustainability.